Doença periodontal como possivel fator de risco para aterosclerose coronaria - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
In the last years, a great amount of information suggested a possible relationship between periodontal disease and cardiovascular disease. Several scientific works showed a significant association between periodontal parameters and cardiovascular problems. The aim of this research went evaluate to oral health and the periodontal disease in humans verifiying if these conditions potentially could be correlated as possible risk factors for coronary artherosclerotic disease. Eighty patients were submitted the coronary angiography and divided in two groups: patients with coronary artherosclerotic disease (n=59) and patients without coronary artherosclerotic disease (n=21). The analyzed variables were age, gender, smoking, alcoholic using, family history of coronary disease, hypertension, diabetes, total cholesterol, LDL, HDL, triglicerides and obesity; reactive C protein, CK, CKMB, ureia, creatinin and number of erythrocytes, leucocytes and lymphocytes. The periodontal exam and of the condition of health and oral hygiene consisted of the following parameters: dental loss, tongue biofilm presence, number of periodontal pockets with clinical depth ³5mm; number of sites with loss of clinical insert ³6mm; gingival index, plaque index, number of patients and sites with exsudate. In the collected exsudates of periodontal pockets were accomplished microbiologic tests and Streptococcus of the group viridans alpha hemolyse and negative catalase were isolated in 43.75% of the samples. The results showed that the cholesterol levels increase was a tendency in the patients with and without coronary artherosclerotic disease with periodontal disease, coming significantly different when compared with the patients without artherosclerotic disease and without periodontal disease (p=0.0389) showing a relationship between periodontal disease and lipid metabolism. The parameters of oral hygiene (p=0.0237) and periodontal condition presented values significantly different when compared the groups (p<0.0001), presenting a difference among the proportions =0.2519 with 95% of the confidence interval of the difference = 0.058 to 0.445 and Odds Ratio=3.913. Suggesting that patients with periodontal disease have 4x larger probability approximately of having coronary problems (p=0.0125).
Keywords: periodontite; aterosclerose; saúde bucal; periodontitis; atherosclerosis; oral health; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA